Surgical Outcomes of Total Anomalous Pulmonary Venous Drainage at Dr. Soetomo General Academic Hospital, Surabaya: A One-Year Case Series: TAPVD Surgical Outcomes in Indonesia - Agustio Putra Hutabarat, Muhammad Caesar Borni; Soebroto, Heroe; Hakim, Arief Rakhman; Akbar, Erdyanto; Pagehgiri, Hari Daswin (Journal of Neonatal Surgery, 2025)
INTRODUCTION Total anomalous pulmonary venous drainage (TAPVD) is a rare anomaly, accounting for 1% to 3% of patients with congenital heart disease. Characterized by the abnormal connection of the pulmonary veins to the systemic venous circulation, rather than to the left atrium. This case series aims to emphasized the significance of early diagnosis, surgical strategy, and outcomes associated with TAPVD. METHODOLOGY Over a one-year period, we treated 5 cases of TAPVD at our institution, involving patients aged one to nine years, with a male-to-female ratio of 1.5:1. The patients exhibited various clinical symptoms including cyanosis, and respiratory distress. Echocardiography was the primary diagnostic method, supported by cardiac catheterization and computed tomography cardiac imaging for detailed anatomical evaluation. Surgical correction was performed in all cases, with techniques tailored to the specific anatomical variations of TAPVD, in this cases supra-cardiac, intra-cardiac, and mixed types. The surgeries aimed to redirect the pulmonary veins to the left atrium and close the interatrial defect. Postoperative care involved intensive management of potential complications like pulmonary hypertension. RESULTS Three out of five cases experienced postoperative complications due to serious preoperative conditions. Nevertheless, this case series revealed a 100% survival rate, with an average ICU stay of 5.7 days and an overall hospital stay averaging 7.7 days. Short-term follow-up revealed significant symptoms improvement, highlighting the importance of timely surgical intervention for achieving favorable outcomes. CONCLUSION This case series underscores the significance of early diagnosis, meticulous surgical strategy, and effective postoperative care in enhancing outcomes for TAPVD.